2015
DOI: 10.1111/papr.12339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Current Density on Nociceptor Activation Upon Electrical Stimulation in Humans

Abstract: Electrical stimulation at high current density using pin electrodes is a sensitive method for investigating "silent" nociceptors, which might therefore preferably be applied in neuropathic pain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Electrically induced pain thresholds recorded from both forearms prior to the patch application were used to calculate the current intensity required for supra‐threshold electrical stimulation (1.5‐fold pain threshold) as this initial level was kept constant throughout the entire experimental period. As described previously (Landmann et al., ), electrical stimulation pulses of 1.5‐fold pain threshold were delivered in five consecutive blocks at 15 s intervals. Each block consisted of 10 monophasic rectangular pulses of 5–10–20–50–100 Hz frequencies, respectively, and frequency‐blocks were applied in randomized order.…”
Section: Methodsmentioning
confidence: 99%
“…Electrically induced pain thresholds recorded from both forearms prior to the patch application were used to calculate the current intensity required for supra‐threshold electrical stimulation (1.5‐fold pain threshold) as this initial level was kept constant throughout the entire experimental period. As described previously (Landmann et al., ), electrical stimulation pulses of 1.5‐fold pain threshold were delivered in five consecutive blocks at 15 s intervals. Each block consisted of 10 monophasic rectangular pulses of 5–10–20–50–100 Hz frequencies, respectively, and frequency‐blocks were applied in randomized order.…”
Section: Methodsmentioning
confidence: 99%
“…Intradermal injection of NGF is known to facilitate action potential generation and conduction (Obreja, et al., 2011; Obreja et al., 2018; Rukwied et al., 2014). In order to induce action potential discharge preferentially in nociceptors we designed an electrode (Landmann et al., 2016) and a stimulus profile (Rukwied et al., 2020) to specifically depolarize mechano‐sensitive C‐nociceptors. A half sine wave constant current stimulus provokes a burst of action potentials (Rukwied et al., 2020) and we found that NGF increased the pain ratings to the most intense amplitude of half sine wave stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Note that with a rectangular stimulation paradigm of 0.25 Hz and 0.5 ms pulse duration the transcutaneous electrical thresholds were >9 mA for C-nociceptor stimulation (electrode covering 30 mm 2 ) (30). If higher current densities are provided at the stimulation sites by using pointed (1 mm diameter) or bipolar (2 mm length, 3 mm distance) pin electrodes (stimulation frequency 1-10 Hz) current intensities exceeding 5 mA are required for C-fiber activation (31,32). Given the low intensities and high frequencies used in the protocols summarized, most likely myelinated A-fibers had been stimulated.…”
Section: Electrically Evoked Itch In Healthy Human Subjectsmentioning
confidence: 99%